Assessment of Role of Communication Competence in Dental Students for Acquiring Social Support - Deshmukh, Neeti P; Pawshekar, Mohini A; Paul, Priyanka (Indian Journal of Community Health, 2025)
Background: Effective primary care provision requires strong social support, which may be enhanced by communication competence. The study proposes to examine the magnitude of perceived social support and communication competence and the role of communication competence in garnering perceived social support. Aim and objectives: To assess communication competence of dental students and the degree of social support they receive. Methodology: The cross-sectional study was conducted at Sharad Pawar Dental College, Wardha. Study population comprised 400 students pursuing their Bachelor’s degree (BDS). Perceived social support was measured using a Multidimensional Scale of Perceived Social Support. The communication competence was assessed by the Self-perceived Communication Competence Scale. Results: Communication competence was the only determinant of perceived social support. For every unit increase in communication competence, the perceived social support increased by 0.018 units. The increase was statistically significant. The model explained 13% variance in the perceived social support, which was statistically significant. Conclusion: Social support is crucial for self-esteem, which is moderated by communication competence. This facilitates leadership efficiency and ultimately serves in the making of a five-star doctor. The present study supports the abovementioned findings and underlines the need to work more on building graduate students’ communication competence through foundation courses.